Rancang Bangun Pembelajaran Doa Sehari-hari untuk Anak Kebutuhan Khusus Berbasis Augmented Reality - Isa Bahroni; Andriansyah Zakaria (Journal of Innovation Information Technology and Application (JINITA), 2020)
AR (Augmented Reality) technology is a combination of 2D, 3D and the real world combined in one object with technology that can be applied as a means of active learning media while learning while playing. Cilacap State Special School (Special School) Cilacap students are children with special needs who are very difficult to memorize and very poor concentration on subjects one of which is the subject of Islam with daily prayer material. In this study the authors designed an Android-based daily prayer learning media that contains animations with Tomy's character learning to read daily prayers. This study aims to help students with special needs in learning to memorize Islamic prayer. The base is applied using AR technology as a medium which is good enough for the media to deliver information to students. This application was designed using the MDLC (Multimedia Development Life Cycle) method. The results of this application run by detecting the target image of several images of daily prayer and then displaying Tomy's animation in the form of 3D reading a prayer. This research produced an AR application that helps visualize memorization of prayers so that it can improve SLB N Cilacap students in memorizing daily prayers.